The Association of MRI Findings and Long-Term Disability in Patients With Chronic Low Back Pain. Issue 5 (June 2021) - Udby, Peter Muhareb; Ohrt-Nissen, Søren; Bendix, Tom; Brorson, Stig; Carreon, Leah Y.; Andersen, Mikkel Østerheden
Study Design: Longitudinal cohort study with 13-year follow-up. Objective: To assess whether long-term disability is associated with baseline degenerative magnetic resonance imaging (MRI) findings in patients with low back pain (LBP). Methods: In 2004-2005, patients aged 18 to 60 years with chronic LBP were enrolled in a randomized controlled trial and lumbar MRI was performed. Patients completed the Roland-Morris Disability Questionnaire (RMDQ) and the LBP Rating Scale, at baseline and 13 years after the MRI. Multivariate regression analysis was performed with 13-year RMDQ as the dependent variable and baseline disc degeneration (DD, Pfirrmann grade), Modic changes (MC), facet joint degeneration (FJD, Fujiwara grade) smoking status, body mass index, and self-reported weekly physical activity at leisure as independent variables. Results: Of 204 patients with baseline MRI, 170 (83%) were available for follow-up. Of these, 88 had Pfirrmann grade >III (52%), 67 had MC (39%) and 139 had Fujiwara grade >2 (82%) on at least 1 lumbar level. Only MC (β = −0.15, P = .031) and weekly physical activity at leisure (β = −0.51, P < .001) were significantly, negatively, associated with 13-year RMDQ-score ( R 2 = 0.31). Conclusion: DD and FJD were not associated with long-term disability. Baseline MC and weekly physical activity at leisure were statistically significantly associated with less long-term disability.